Petrogenesis of Upper Paleozoic post-collisional peraluminous leucogranites, Sierra de Ancasti, northwest Argentina - Toselli, Alejandro Jose (2011)
The Santa Rosa and Sauce Guacho plutons are two post-collisional peraluminous Late Devonian to Early Carboniferous leucogranites that intruded the banded schists of the Ancasti Formation.The leucogranites are composed of microcline phenocrysts along with quartz, plagioclase,muscovite, biotite, ilmenite, tourmaline, apatite, monazite and zircon. Their geochemical compositionis consistent with S-type granites and mineralogically they belong to MPG granites (muscoviteperaluminousgranites). It is proposed that granite magma generation was related to shear zones thatconcentrated fluids in the metasedimentary crust during a collision or transcurrent tectonics. U-Pbanalyses on monazite gave an age of 369.8 ± 5.3 Ma, while Sm/Nd isotopic data yield εNd(t) values of-5.3 for Sauce Guacho and -5.7 for Santa Rosa indicating crustal provenance. Nd model ages between1,544 and 1,571 Ma are within the range of magmatic rocks from the Lower Ordovician FamatinianArc in the Central Sierras Pampeanas.